Differences and Similarities between Impulse Buying and Variety Seeking: A Personality‐based Perspective. Issue 1 (January 2016) - Olsen, Svein Ottar; Tudoran, Ana Alina; Honkanen, Pirjo; Verplanken, Bas
ABSTRACT: Although personality is a key determinant of consumer purchasing decision making, the role of personality traits in impulse buying and variety seeking is not conclusive. This research uses a personality perspective to determine the unique associations among impulse buying tendency (IBT), variety seeking tendency (VST), and the Big Five personality traits within one integrated framework. Based on data from a nationally representative sample of 1644 Norwegian adults, the results show that while IBT and VST might be correlated, they differ significantly with respect to two major personality aspects: "neuroticism" and "openness to experience." Specifically, the present study indicates that neuroticism predicted IBT positively and VST negatively, while openness was a strong predictor of VST and unrelated to IBT.